Diffuse large B-cell lymphoma of the endometrium: an unusual site for primary presentation. Issue 1 (2nd January 2019) - Wadee, Reubina
Abstract : Diffuse large B-cell lymphomas are fairly common adult haematolymphoid malignancies. Approximately 40% of such tumours may present in an extranodal site. These lymphomas are, however, infrequently identified in the female genital tract and even more rarely, identified in the endometrium. The histopathological features and molecular findings of endometrial diffuse large B-cell lymphoma are discussed herein. A 36-year old female presented with per vaginal bleeding. She underwent an endometrial curettage, which demonstrated morphological and immunophenotypical features of a diffuse large B-cell lymphoma. Amplification of the immunoglobulin heavy chain (IgH) gene by polymerase chain reaction (PCR) confirmed B-cell clonality. Epstein–Barr encoding region (EBER) in-situ hybridisation was positive in tumour cells. Fluorescent in-situ hybridisation (FISH) for the detection of BCL6 and MYC gene rearrangement as well as for the detection of the t(14;18) (q32;q21) translocation was performed, all of which yielded negative results. Unfortunately, the patient was lost to follow-up. Whilst diffuse large B-cell lymphoma is not a commonly identified tumour within the uterine cavity, it should be included in the differential diagnosis of endometrial neoplastic infiltrates so as not to misdiagnose this tumour. This facilitates rapid commencement of further management for the patient.